Synthetic Aperture Cardiac Imaging with Reduced Number of Acquisition Channels. A Feasibility Study - TASINKEVYCH, Yuriy; LEWANDOWSKI, Marcin; KLIMONDA, Ziemowit; Walczak, Mateusz (Archives of Acoustics, 2018)
Commercially available cardiac scanners use 64–128 elements phased-array (PA) probes and classical delay-and-sum beamforming to reconstruct a sector B-mode image. For portable and hand-held scanners, which are the fastest growing market, channel count reduction can greatly decrease the total power and cost of devices. The introduction of ultra-fast imaging methods based on plane waves and diverging waves provides new insight into heart’s moving structures and enables the implementation of new myocardial assessment and advanced flow estimation methods, thanks to much higher frame rates. The goal of this study was to show the feasibility of reducing the channel count in the diverging wave synthetic aperture image reconstruction method for phased-arrays. The application of ultra-fast 32-channel subaperture imaging combined with spatial compounding allowed the frame rate of approximately 400 fps for 120 mm visualization to be achieved with image quality obtained on par with the classical 64-channel beamformer. Specifically, it was shown that the proposed method resulted in image quality metrics (lateral resolution, contrast and contrast-to-noise ratio), for a visualization depth not exceeding 50 mm, that were comparable with the classical PA beamforming. For larger visualization depths (80–100 mm) a slight degradation of the above parameters was observed. In conclusion, diverging wave phased-array imaging with reduced number of channels is a promising technology for low-cost, energy efficient hand-held cardiac scanners.